2018
DOI: 10.5194/nhess-18-2969-2018
|View full text |Cite
|
Sign up to set email alerts
|

Local-scale post-event assessments with GPS and UAV-based quick-response surveys: a pilot case from the Emilia–Romagna (Italy) coast

Abstract: Abstract. Coastal communities and assets are exposed to flooding and erosion hazards due to extreme storm events, which may increase in intensity due to climatological factors in the incoming future. Coastal managers are tasked with developing risk-management plans mitigating risk during all phases of the disaster cycle. This necessitates rapid, time-efficient post-event beach surveys that collect physical data in the immediate aftermath of an event. Additionally, the inclusion of local stakeholders in the ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…At present, there is not an official regional (or national) standard for data collection in the aftermath of an extreme coastal event, in order to measure flood levels and identify, collect and rigorously catalog the losses in monetary terms or structural/content damage. Standard datacollection protocols should be based on scientific studies already available at local level (e.g., Duo et al, 2018), in order to collect the necessary information that is of foremost importance to develop damage models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there is not an official regional (or national) standard for data collection in the aftermath of an extreme coastal event, in order to measure flood levels and identify, collect and rigorously catalog the losses in monetary terms or structural/content damage. Standard datacollection protocols should be based on scientific studies already available at local level (e.g., Duo et al, 2018), in order to collect the necessary information that is of foremost importance to develop damage models.…”
Section: Discussionmentioning
confidence: 99%
“…The main coastal hazards are beach erosion and inundation that cause sediment loss and beach width reduction, along with damages to coastal structures and infrastructures. A major event occurred on 5-7 February 2015 (Hs = 4.6 m, Tp = 9.9 s, wave dir = ENE -measured at the Cesenatico wave rider buoy at the peak of the storm; max water level = 1.2 m measured at Porto Corsini tide gauge, Figure 1; Duo et al, 2018). This caused the extensive inundation of landward areas and impressive beach erosion.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that computing resources, software, data, and algorithms are fully capable of analyzing a large volume of data at multiple spatial scales to derive an understanding of the complex changes and the interplay among the various coastal processes at work in this area. Future research could build upon this multi-scale approach by using imagery obtained from unmanned aerial systems (UASs) at a very local scale where land cover and shoreline changes have been identified [41][42][43][44][45]. Instrumentation aboard unmanned aerial vehicles (UAVs) can provide excellent spatial resolution as well as multispectral bands; however, the coverage is limited because of battery time for overflights and access to launch and retrieve equipment can be problematic [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The geomatic surveying methods, such as aero photogrammetric surveys [7,8], unmanned aerial vehicle (UAV) [9][10][11][12][13][14][15], remote sensing with satellite images [12,16], airborne light detection and ranging (LiDAR) [17][18][19][20][21][22], synthetic aperture radar (SAR) [23,24], video systems [25][26][27][28][29] are widespread techniques to measure wide areas, generate digital terrain models (DTMs) and maps, and to quantify coastal changes by multi-temporal comparisons.…”
Section: Introductionmentioning
confidence: 99%